Endovascular thrombectomy beyond 12 hours of stroke onset: a stroke network's experience of late intervention. (19th February 2018) - Motyer, Ronan; Thornton, John; Power, Sarah; Brennan, Paul; O'Hare, Alan; Looby, Seamus; Williams, David J; Moynihan, Barry; Murphy, Sean
Abstract : Background: Selected patients with proximal anterior circulation ischemic stroke who demonstrate limited infarct and sufficient penumbra may benefit from endovascular thrombectomy (EVT) beyond conventional time limits. Objective: To perform a retrospective review of all cases of EVT performed at our institution for proximal anterior circulation acute ischemic stroke with onset >12 hours. Materials and methods: Patients were assessed with non-contrast CT brain and multiphase CT angiography, with Alberta Stroke Program Early CT Score (ASPECTS) and collateral grade informing patient selection. Data, including patient demographics, workflow, neuroimaging findings, procedural details, recanalization rates, and 90-day functional outcomes, were collected. Results: Of the 542 consecutive endovascular thrombectomy cases performed during the study period, 25 (4.6%) were >12 hours from stroke onset. Median age was 69 years (IQR 55–80), median National Institute of Health Stroke Scale score on presentation was 14 (IQR 11–18.5), median ASPECTS was 8 (IQR 8–9), and rate of moderate–good collateral status was 96% (n=24). Median time to groin puncture was 14 hours 40 min (IQR 12 hours 36 min – 16 hours 18 min). Rate of successful recanalization (modified Thrombolysis in Cerebral infarction 2b–3) was 88% (n=22). Rate of functional independence (90-day modified Rankin Scale score 0–2) was 52% (n=13). There were no cases of symptomatic intracranial haemorrhage and 90-day mortality rate was 12% (n=3). Conclusion: With the use of ASPECTS and collateral grade to guide patient selection, good functional outcome with acceptable safety parameters may be achieved in patients undergoing EVT beyond 12 hours from stroke onset.